Assays to Measure ER-Associated Degradation in Yeast - Tran, Joseph R. (2012)
Endoplasmic reticulum-associated degradation (ERAD) is a process that clears the early secretory pathway of misfolded proteins. Though ERAD is of basic biological importance, the clinical importance of this pathway is emphasized by the fact that mutations that render a protein subject to the ERAD quality control pathway underlie the cause of several diseases. The yeast, Saccharomyces cerevisiae, is a valuable and frequently used model system to study biological processes, such as ERAD, as it is a relatively simple model system for which numerous biochemical and genetic tools are available. In addition, the ERAD system is highly conserved between yeast and man. In this chapter, we describe two methods for the analysis of model substrates that undergo catabolism via the ERAD pathway using S. cerevisiae. In particular, we will describe non-radioactive degradation assays and the analysis of substrate ubiquitylation in vivo with or without the use of ubiquitin overexpression systems. We also describe technical hurdles, which we have encountered in our research, and highlight remedies to overcome them.